Assessment of Impact of Early Stroke Rehabilitation on Hip Joint Mobility of the Affected Leg in Patients after Cerebrovascular Accidents - Wioletta Łubkowska; Bożena Mroczek; Tomasz Zdeb (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2015)
One of the main priorities of stroke rehabilitation is regaining patients’ independence in basic everyday activities. This paper is aimed at assessing impact of early stroke rehabilitation on hip joint mobility of the affected leg in patients after cerebrovascular accidents. The study included 30 subjects (13 men and 17 women) aged on average ±66.1, with hemiparesis, who were treated at the stroke unit and participated in a 4-week rehabilitation program. Measurements of passive and active motion ranges were conducted with a goniometer in both limbs: healthy and affected ones by stroke. There were statistically significant differences in motion ranges between healthy and affected limbs. Examination I revealed that affected limbs amounted to only 40% of physiological range, while in Examination II, the result reached 73%. The most significant motion limitations were noted in terms of bending, adduction and internal rotation, while the least significant in terms of external rotation and abduction. Exercises used during early stroke rehabilitation of hemiparesis patients considerably increased active motion ranges and maintained passive motion ranges in the hip joint of the affected limb. Patients with right-sided hemiparesis experienced much better improvement in hip joint motion of the affected limb. The 4-week period was insufficient to mobilize patients and help them regain full active mobility in the hip joint of the affected limb. These patients required further physiotherapy, until they fully regained functionality.